A drug delivery analysis of large molecules in ocular vitreous chamber: Dependency on saccadic movements after intravitreal injection. (August 2020) - Ferroni, Marco; De Gaetano, Francesco; Cereda, Matteo Giuseppe; Boschetti, Federica
Highlights: A drug delivery analysis of large molecules in ocular vitreous chamber. Implementation of saccadic movements after an intravitreal injection. Two different injection sites of drug bolus are analyzed. Drug distribution in presence or absence of saccades is computed. Abstract: The purpose of this study is to investigate the effect of vitreous sloshing induced by saccades on the intravitreal delivery of large molecule drugs. The vitreous body was considered in its age-related liquefaction condition. Fluid dynamics and large molecule distribution were described by the coupling of mass conservation's and Fick's laws with continuity and momentum equations for a Newtonian incompressible fluid in a 3D unsteady analysis. Two injection sites were analyzed, in both the mixing effect of a 50° periodic saccade leads to uniform drug distribution in 30 s of simulation, the initial bolus site being left after 3 s of simulation. In absence of saccadic movements, the dominant transport contribution is the diffusive one and large molecules hardly reach their uniform distribution inside the vitreous cavity. A model describing the intravitreal distribution of large molecules in presence of saccades was developed, improving the understanding of drug transport mechanism after an intravitreal injection and highlighting how advection contribution enhances its distribution in the vitreous chamber.